Structure of the leaf litter frog community in an area of Atlantic Forest in southeastern Brazil - Natália Vagmaker; Juliane Pereira-Ribeiro; Átilla Colombo Ferreguetti; Alex Boazi; Rayanne Gama-Matos; Helena Godoy Bergallo; Carlos Frederico Duarte Rocha (Zoologia (Curitiba), 2020)
Different spatial and temporal factors can influence the species richness and abundance of leaf anurans that are fundamental for the ecosystem functioning, as they act as predators and integrate the trophic chain as prey of other animals. There are relatively few studies that aimed to understand the spatio-temporal variation and the influence of environmental factors on leaf litter communities. We studied parameters of the anuran community living in the forest leaf litter in the Duas Bocas Biological Reserve (DBBR), Espírito Santo, Brazil. We sought to understand the extent to which richness, abundance, biomass and density varied between two locations with different stages of preservation (primary and secondary forest). In addition, we tested the effect of temperature and local humidity on abundance. We conducted the samplings monthly from October 2017 to September 2018, establishing 98 4 x 4 m plots (16 m2 each) demarcated on the DBBR forest leaf litter. We measured temperature (°C) and relative air humidity (%), and each plot was carefully surveyed by four observers. We tested for differences in anuran density between the two sampled locations and estimated the effects of environmental variables in the community. We recorded 102 individuals of anurans from 11 species belonging to eight families. The DBBR anuran community parameters significantly differed between the two studied locations, with the highest values of anuran richness and abundance occurring in the area covered by primary forest, probably due to differences in the preservation of each area. However, temperature and humidity did not affect the abundance of anurans in the sampled areas. Our results provide the first information about spatial variation and influence of environmental factors, directed to the community of leaf litter anurans in DBBR, and represents the second study on this group of anurans in the state of Espírito Santo.